Effects of ruminal pH and subacute ruminal acidosis on milk yield and composition of Holstein cows in different stages of lactation - KITKAS, G. C.; VALERGAKIS, G. E.; KRITSEPI-KONSTANTINOU, M.; GELASAKIS, A. I.; ARSENOS, G.; KALAITZAKIS, E.; PANOUSIS, N. (Journal of the Hellenic Veterinary Medical Society, 2019)
Subacute ruminal acidosis (SARA; implying a rumen fluid pH between 5.5 and 5.0), is one of the most important metabolic diseases of dairy cows. In this study, the effect of SARA and rumen fluid pH on milk yield and composition was assessed in dairy cows under field conditions, with repeated measurements in the same cows, at different stages of lactation. Rumenocentesis was performed in 83 Holstein cows of a commercial herd at 30, 90, and 150 days in milk (DIM). Rumen fluid pH was measured on-site using a portable pH-meter. Milk yield was also recorded at the same days. Milk samples were analyzed for fat, protein, lactose and total solids content. For the statistical analysis, mixed linear regression models were used. Prevalence of SARA was 48.2%, 53.8% and 65.3% at 30, 90 and 150 DIM, respectively. There was a significant negative effect of SARA and decreased rumen fluid pH on milk fat content; SARA was associated with a decrease of milk fat content by 0.22%, while a one-unit increase of rumen fluid pH, even within the normal range, was associated with a 0.28% increase of milk fat content and 0.44% increase of milk total solids content. There was no effect of SARA on milk yield or protein, lactose and total solids content. In conclusion, under field conditions, SARA and decreased rumen fluid pH reduce milk fat content.